IJCM_18A: A Cross-sectional study on prevalence of pregnancy related anxiety among antenatal mothers attending Rural Primary Health Center, Kancheepuram - Priyadharshini S; Chitra (Wolters Kluwer Medknow Publications, 2024)
Background: With declining rates of maternal mortality worldwide, its time to recognize the importance of addressing morbidity as well. When compared with general anxiety, pregnancy-related anxiety appears to be a stronger determinant for poor obstetric consequences. Complications include miscarriage, low birth weight, impaired cognitive and physical fetal development, and possibly death. Objectives: To assess the prevalence of pregnancy related anxiety with severity and the associated factors. Methodology: A cross-sectional on was conducted among 113 antenatal mothers attending antenatal clinic (Tuesdays)in Kundrathur Rural Primary Health Centre by consecutive sampling. Data was collected by interviewer administering a validated and structured questionnaire PRAQ R2(Pregnancy Related Anxiety Questionnaire Revised 2) and statistical analysis was done using IBM SPSS version 25. Results: Among 113 antenatal mothers mean age was 25.19+4.2 years, 69.9% are primi gravida, 50.4% said that current pregnancy is planned. All of the mothers having complications in current pregnancy (22.1%) had pregnancy related anxiety. The mean scores of pregnancy related anxiety domains were 7.6 out of 15 for fear of giving birth, 4.9 out of 15 for concern of own appearance, and 10.9 out of 12 for worries about bearing a handicapped child. Nearly 89.4% of mothers have pregnancy-related anxiety with most of them having low severity anxiety (44.2%). The factors associated with pregnancy related anxiety (p < 0.05) were primi gravida and those in second and third trimester. Conclusion: A majority of the participants are experiencing pregnancy related anxiety with most of them having low severity anxiety worrying about outcome of birth. It's predictors included Primigravida and those in second and third trimester. Pregnancy-related anxiety should be diagnosed early during routine antenatal mothers for better maternal and fetal outcomes